2003
DOI: 10.1046/j.1537-2995.2003.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating RBC volume, measured with biotinylated RBCs, is superior to the Hct to document the hematologic effects of delayed versus immediate umbilical cord clamping in preterm neonates

Abstract: Because true hematologic effects of delayed versus immediate cord clamping may not be apparent or may be misinterpreted, when based on indirect measurements of Hct or calculations of circulating RBC volume, it is important to measure circulating RBC volume directly-as done with autologous, biotinylated RBCs-to document whether delayed cord clamping truly results in a transfer of significant quantities of RBCs from placenta to neonate. The clinical benefits and potential toxicities of increased RBC transfer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 9 publications
6
56
1
Order By: Relevance
“…Regarding the consequence of a rapid change in the hematocrit level that normally occurs during the first 24 hours of life, comparing late with early cord clamping, the risk of anemia was decreased with late cord clamping at 24 to 48 hours after birth [24,25]. Van Rheenen [23,26] showed that the most important finding was that the beneficial effects of late cord clamping appear to extend beyond the early neonatal period and it is a physiological and inexpensive means of enhancing hematologic status, preventing anemia over the first 3 months of life and enriching iron stores and ferritin levels for as long as 6 months.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the consequence of a rapid change in the hematocrit level that normally occurs during the first 24 hours of life, comparing late with early cord clamping, the risk of anemia was decreased with late cord clamping at 24 to 48 hours after birth [24,25]. Van Rheenen [23,26] showed that the most important finding was that the beneficial effects of late cord clamping appear to extend beyond the early neonatal period and it is a physiological and inexpensive means of enhancing hematologic status, preventing anemia over the first 3 months of life and enriching iron stores and ferritin levels for as long as 6 months.…”
Section: Figurementioning
confidence: 99%
“…Based on the above Figure Strauss [24] stressed that delaying clamping of the umbilical cord for at least 2 minutes after birth consistently improved feto placental circulation and both the short-and long-term hematologic and iron status of full term infants.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…29 Preterm infants (30-36 weeks' gestation at birth) randomized to delayed cord clamping (at 1 minute of age) had larger circulating red blood cell (RBC) volume, no difference in hematocrit at birth, but higher hematocrit at 7, 14, 21, and 28 days of age compared with preterm infants randomized to immediate cord clamping within 5 seconds of birth. 30,31 There was no increase in polycythemia or jaundice in the delayed cord clamping groups. 31 Another randomized controlled trial found that preterm infants assigned to delayed cord clamping (30-90 seconds after birth) had significantly higher blood volumes regardless of mode of delivery (cesarean section or vaginal delivery) compared with infants who had immediate cord clamping.…”
Section: Preterm Infantsmentioning
confidence: 80%
“…Nevertheless, the use of radioactive substances for research in infants would be considered ethically unacceptable in the 21st century. Fortunately, biotin has been developed as a safe, nonradioactive RBC label for studies of RCV and RBC survival in infants (10,11,14,24,25), allowing continued research in this important area.…”
Section: Red Cell Volume Changes In Vlbw Infantsmentioning
confidence: 99%